Service provision by agri-cooperatives engaged in high value markets - Stoian, D.; Foundjem, D.; Blare, T.; Donovan, D. (2016)
This note presents a practical approach by which cooperatives strengthen their ability to deliver impactful and financially sustainable services. In doing so, it recognises the challenges faced by cooperatives to design services that both meet the different needs of members and are financially sustainable.